156 Review of Outcomes of a Dedicated Geriatric Surgical Liaison Service. (16th September 2019) - Coary, Roisin; McCarthy, Kathryn; Sumrien, Haytham; Shipway, David
Abstract: Background: In the United Kingdom, the 2010 National Confidential Enquiry into Patient Outcome and Death report 'An Age Old Problem' outlined significant shortcomings in the perioperative care of older people. Other than hip fractures, the care of older patients under surgical specialities is largely devoid of routine geriatrician input. In August 2018, we introduced daily geriatric reviews (GR) on the gastrointestinal surgical wards, aiming to improve length of stay (LOS) and mortality. Methods: All acute general surgery admissions for patients ≥70 years were reviewed between September and October 2017 (pre-introduction) and 2018 (post-introduction), and outcomes compared. For 2018, comparisons were also made between those who had GR and those who didn't. Results: There were 173 admissions in 2017, vs 190 in 2018. In both 2017 and 2018, median age was 80, median LOS was 4 days, and clinical frailty scale (CFS) 4. Twenty-two percent (38/173) of patients had a surgical procedure in 2017, vs 33% (63/190) in 2018. Inpatient mortality was 8% (13/173) in 2017 (median CFS 6), vs 6% (11/190) in 2018 (median CFS 6). In 2018, 21% (40/190) of patients had GR: median time to review 3 days. 54% (n=22) of the patients with GR underwent a surgical procedure, 37% (n=15) were admitted to ICU, and inpatient mortality was 5% (n=2), vs 28% (n=42), 4% (n=6) and 6% (n=9) respectively for those without GR. 30 day readmission for those with GR was 12.5% (n=5), vs 18.4% (n=28) for those not seen. Conclusion: While more surgical procedures were performed in 2018 (post-introduction), overall LOS remained unchanged and improved mortality was observed compared to 2017. Geriatricians are seeing more post-operative and ICU patients, and despite presumed increased complexity, both mortality and readmission rates remain low. Screening for frailty and specific inclusion criteria may improve rates of GR.